일본 요양병원 의료서비스 품질이 입원환자 만족도와 재이용의도에 미치는 영향 - 황선자(Sun-Ja Hwang) (한국콘텐츠학회논문지, 2018)
The purpose of this study is to examine the effect of the medical service quality of the nursing hospital on the inpatients' satisfaction, reuse intention and to verify the mediating effect of the inpatients' satisfaction. The subjects of this study were 255 male and female inpatients in Hiroshima in Japan. The collected data were used as a model of path coefficients obtained through analysis of covariance structure and hypothesis test. As a result of verification, level of medical team and medical service, reception, facility and fee of the medical service quality of the nursing hospital perceived by the inpatients showed a statistically significant positive correlation with the inpatients' satisfaction. The inpatients' satisfaction showed a statistically significant positive correlation with their reuse intention. The level of medical team and medical service, reception, facility and fee of the medical service quality of the nursing hospital perceived by the inpatients shows a statistically no significant positive correlation with the reuse intention. But, they show a statistically significant positive correlation with the reuse intention with the mediating effect of the inpatients' satisfaction. Finally, the result of this study is to confirm the effect of the medical service quality on the inpatients' satisfaction, reuse intention of the nursing hospital. In this process, it is meaningful to verify the role and function of medical service quality of the nursing hospital. 본 연구에서는 요양병원의 의료서비스 품질이 입원환자 만족과 재이용의도에 미치는 영향을 검증하고, 이 과정에서 입원환자 만족의 매개효과를 검증하였다. 본 연구의 대상은 일본 히로시마 소재 요양병원 입원환자 255명으로서, 수집된 자료를 이용하여 공분산구조분석을 통해 얻은 경로계수로 모형과 가설 검정을 실시하였다. 검증 결과, 입원환자인 고객이 지각하는 의료서비스 품질의 의료진 및 의료수준, 응대성, 시설 및 요양비용 품질 요인은 입원환자 만족에 각각 통계학적으로 유의하게 정(+)의 관계를 보였다. 그리고 입원환자 만족과 재이용의도 간의 경로계수는 정(+)의 관계를 보였다. 한편, 입원환자인 고객이 지각하는 의료서비스 품질의 의료진 및 의료서비스 품질, 응대성, 시설 및 요양비용 품질 요인은 입원환자 만족에 각각 통계학적으로 유의한 영향을 미치지는 않았으나, 입원환자 만족을 매개로 하여 유의한 영향을 미치는 것으로 나타났다. 본 연구의 결과는 요양병원산업 차원의 마케팅전략에 있어서, 의료서비스 품질을 반영하여, 요양병원 이용자만족에 미치는 영향을 확인하고, 이 과정에서 요양병원 의료서비스 품질의 역할 및 작용을 검증하였다는데 의의가 있다.